Environmental Management Strategy In Schools: A Case Study At SMA Negeri 1 Bekasi, West Java - Situmorang, Marningot Tua Natalis (Universitas Malikussaleh, 2020)
This paper aims to find out about school environmental management strategies in West Java secondary schools. To guide the study, three research questions were formulated. This is achieved by administering a structured questionnaire in a random sample school of 100 students. The findings show regular lawn cleaning, school complex sweeping and painting, landscaping and flower planting, good drainage and garbage disposal are strategies adopted for managing school environments. While the lack of gardeners to keep the school complex clean, erosion, students and teachers are not responsive to environmental problems, difficulties in instilling students' environmental values due to different care of homes, lack of funds for procurement of work tools/equipment and challenges of waste disposal are some of the challenges. Identified in the management of the school environment. For a better and better school environment for good academic practice, school environmental management team, plans for drainage and waste disposal, consideration of school locations for new schools, janitorial work, terminal orientation programs, development of curricula on environmental management, inspections and school competitions and awards are recommended